Aeroallergens, air pollutants, and chronic rhinitis and rhinosinusitis. Issue 3 (1st September 2018) - London, Nyall R.; Lina, Ioan; Ramanathan, Murugappan
Abstract : Chronic rhinitis and rhinosinusitis are among the most common conditions worldwide with significant morbidity and decreased quality of life. Although the pathogenesis of these conditions is multifactorial, there has been increasing evidence for the role of environmental factors such as aeroallergens and air pollutants as initiating or exacerbating factors. This review will outline the current literature focusing on the role of aeroallergens and air pollution in the pathogenesis of chronic sinonasal inflammatory conditions.